Mycobacterium shimoidei: an uncommon non-tuberculous infection in a UK patient. (2nd February 2018) - Braganza Menezes, Darryl A; Dedicoat, Martin J; Robertson, Alastair
Abstract : We present the case of a 69-year-old man with significant respiratory comorbidities who presented with slow growing pulmonary nodules which cavitated. Subsequent sputum sampling grew Mycobacterium shimoidei, a non-tuberculous mycobacterium species and an uncommon cause of infection in the UK. We describe the diagnostic process and subsequent treatment regimen.